2019
DOI: 10.1177/0967391119853956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological study of short glass fiber-reinforced PA 66

Abstract: Tensile, flexural, wear, and friction behaviors of polyamide 6.6 (PA 66) reinforced by different weight fractions of short glass- iber were investigated. Three-point bending flexural tests in addition to monotonic tensile tests were carried out to determine the mechanical behavior. Reciprocating friction tests were carried out without lubrication under ambient conditions. A ball-on-flat contact configuration was adopted for all tests. Reciprocating wear tests were carried out against a silicon carbide abrasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Among a variety of fillers, glass fibers are extensively preferred owing to their ability of increasing the stiffness and heat resistance of the composite as well as their relatively low processing costs [10]. Addition of glass fibers into PA 66 matrix up to a certain ratio leads to a large amount of improvement in the mechanical properties [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Among a variety of fillers, glass fibers are extensively preferred owing to their ability of increasing the stiffness and heat resistance of the composite as well as their relatively low processing costs [10]. Addition of glass fibers into PA 66 matrix up to a certain ratio leads to a large amount of improvement in the mechanical properties [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of GFRPA66 with 35 wt.% reinforcement, the COF decreases under all load and sliding velocity conditions attributed to the transition in material’s behavior from ductile to fragile [ 29 , 46 , 47 ]. As the glass fiber weight increases in the matrix, the glass fiber carries all of the friction load and the transfer film available on specimen surface maintains relatively lesser temperature between pin and steel disc surface.…”
Section: Resultsmentioning
confidence: 99%
“…At low load and low sliding speeds, the coefficient of friction and wear becomes high, but as the load increases within the elastic limit, the friction coefficient decreases. With a further increase in the load beyond the elastic limit, the friction coefficient may increase due to the increase in the plastic deformation [ 29 ]. However, the tribological properties are found to be lower while using a glass fiber reinforced polymer composite with 30 weight % glass fiber and 6 wt.% nylon (30 wt.% GFR and 6 wt.% nylon) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that wear resistance of composites increased with GF content. As the mechanical and tribological behaviors of GFRP composites are improved, their usage areas are increasing day by day and they are subjected to different processing methods [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%